BATAM HOME CHEFS WEBSITE UNTUK MEMPERLUAS JANGKAUAN KONSUMEN DI SEKUPANG BATU AJI PADA ERA REVOLUSI 4.0 - Evi Silvana Muchsinati; Oda IB Hariyanto; Hendi Hendi; Muhammad Tan Abdul R.H; Natalia Lorien; Septia Febriani; Metta Tjia; Ayu Widia Sari; Aqika Nisa Fadillah; Chichi Nabilah; Wulan Angreni; Febrika Febrika (National Conference for Community Service Project (NaCosPro), 2020)
Problems of micro small and medium enterprises (MSMEs) in Batam in doing business when the corona pandemic has a bad impact on small traders, therefore the author makes a website that can be reached by all groups, both teenagers and adults. This website contains details of the products sold, the address, and personal contact of the merchant. This website was created aiming to help or introduce their products to other consumers to be better known. This article is based on data from direct interviews and the results of questionnaires given to SMEs. The area that the writer took as a place of research is Sekupang and Batu Aji Districts, Batam City. This research involved the Revolutionary group and the result was that the Micro Small and Medium Enterprises (MSMEs) who used the Batam Home Chef's website in promoting their merchandise felt helped because their merchandise had already begun to be recognized by many people and there was an increase in sales. Besides that, the results of the testimony conclude that the buyers responded well, positively, and supported the Batam Home Chef's website and MSMEs. Besides that, the feedback provided was also good, even the MSMEs wanted to create a menu of tastes and ordinary appearance. be unique following the testimony that has been given previously. Therefore the testimony is very helpful for the initial development to the peak of the success of the Batam Home Chef's website and MSMEs